EFFECTIVENESS OF DARK CHOCOLATE AND GINGER ON PAIN REDUCTION SCALE IN ADOLESCENT DYSMENORHEA - Rizky Amelia; Sandy Isna Maharani (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2017)
Pain during menstruation (dysmenorrhea) are the most common complaints in women. To reduce pain during menstruation (primary dysmenorrhea) there are several ways including the use of drugs - drugs analgesic, anti-inflammatory, the use of herbal remedies, relaxation techniques, exercise period, as well as massage therapy. The study aims to determine the effectiveness of consumption of dark chocolate and ginger to reduce the scale of pain in primary dysmenorrhea. This type of research is a Quasi experiment, the type of study design pretest - posttest with control group. Respondents in this experiment is a student hostel Bhakti Husada Polytechnic of Semarang Kemenkes a level 1 each - each group of 17 people for giving dark chocolate, Ginger and Control. The instruments used are NRS (Numerik Rating Scale). Data was analyzed by univariate and bivariate.Obtained results showed p-value of 0.029 (α 0.05) showed that there were significant differences between awarding dark chocolate and Ginger to decrease menstrual pain compared to the control group. Dark chocolate and ginger can be a complementary therapy to cope with menstrual pain.Pain during menstruation (dysmenorrhea) are the most common complaints in women. To reduce pain during menstruation (primary dysmenorrhea) there are several ways including the use of drugs - drugs analgesic, anti-inflammatory, the use of herbal remedies, relaxation techniques, exercise period, as well as massage therapy. The study aims to determine the effectiveness of consumption of dark chocolate and ginger to reduce the scale of pain in primary dysmenorrhea. This type of research is a Quasi experiment, the type of study design pretest - posttest with control group. Respondents in this experiment is a student hostel Bhakti Husada Polytechnic of Semarang Kemenkes a level 1 each - each group of 17 people for giving dark chocolate, Ginger and Control. The instruments used are NRS (Numerik Rating Scale). Data was analyzed by univariate and bivariate.Obtained results showed p-value of 0.029 (α 0.05) showed that there were significant differences between awarding dark chocolate and Ginger to decrease menstrual pain compared to the control group. Dark chocolate and ginger can be a complementary therapy to cope with menstrual pain.